Kodifikasi dan Eksistensi Ilmu Hukum dalam Perkembangan Hukum Modern - Made Jody Januarta (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Law plays a fundamental role in creating order, balance, certainty, and benefit in social and state interactions. Legal science, as a dynamic discipline, continues to evolve along with its object of study, based on ethical, moral, and aesthetic principles. This article aims to analyze the relationship between legal codification as an effort to systematize and ensure legal certainty, and the existence and evolution of legal science in the context of modern legal development. This research adopts a normative legal method, focusing on the examination of primary and secondary legal materials, as well as legal analysis as norms and texts. The findings show that legal codification, which emerged from the need for legal certainty and unity, was greatly influenced by Enlightenment political thought, such as the concept of the separation of powers and the doctrine of popular sovereignty. Meanwhile, legal science, rooted in the philosophical foundations of ontology, epistemology, and axiology, faces challenges between theoretical depth and practical demands, yet remains steadfast in its authentic goal of achieving justice. The development of modern law demands a balance between the formal certainty offered by codification and the dynamic nature of legal science in achieving justice amid societal complexity, driving continuous adaptation and reflection.